2015
DOI: 10.1097/jcn.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Negative Emotions in Individuals With Coronary Heart Disease

Abstract: Many individuals with coronary heart disease (CHD) experience disease-related anxiety, depressive symptoms, and anger. Spirituality may be helpful to cope with these negative emotions. Research findings on the role of spirituality in dealing with negative emotions are inconsistent. In this study, we examined the associations between 7 dimensions of spirituality (ie, meaningfulness, trust, acceptance, caring for others, connectedness with nature, transcendent experiences, and spiritual activities) and negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
1
15
0
2
Order By: Relevance
“…While there is extensive Western literature on spirituality/religion in palliative care, the literature from Indonesia is limited. Only four studies could be identified related to spirituality/religion in the general care setting, three studies explored perceptions and attitudes of health‐care professionals toward spirituality (Herlianita, Yen, Chen, Fetzer, & Lin, ; Lucchetti et al ., ; Ramakrishnan et al ., ), and one study measured spirituality in patients with coronary heart disease (Ginting, Naring, Kwakkenbos, & Becker, ). These studies do not provide a picture of spirituality/religious factors in play in the palliative care context.…”
Section: Introductionmentioning
confidence: 99%
“…While there is extensive Western literature on spirituality/religion in palliative care, the literature from Indonesia is limited. Only four studies could be identified related to spirituality/religion in the general care setting, three studies explored perceptions and attitudes of health‐care professionals toward spirituality (Herlianita, Yen, Chen, Fetzer, & Lin, ; Lucchetti et al ., ; Ramakrishnan et al ., ), and one study measured spirituality in patients with coronary heart disease (Ginting, Naring, Kwakkenbos, & Becker, ). These studies do not provide a picture of spirituality/religious factors in play in the palliative care context.…”
Section: Introductionmentioning
confidence: 99%
“…paradigm described as integral, spiritual teachers, psychologists, health care providers, and theorists have noted that attending to physical, mental, emotional, and spiritual aspects of being in an integrated fashion, particularly in the context of community, may be optimal for achieving psychological well-being (Aurobindo, 1993;Engel, 1977;Farias, Underwood, & Claridge, 2013;Ferrer, 2003;Ginting, Naring, Kwakkenbos, & Becker, 2014;Koenig et al, 2014;Leonard & Murphy, 2005;Schlitz et al, 2005;Short, 2006;Wilber, Patten, Leonard, & Morelli, 2008).…”
mentioning
confidence: 99%
“…In addition, Martínez and Custódio revealed strong negative association between spiritual well‐being and poor mental health or presence of psychological stress among Brazilian patients receiving hemodialysis. These findings reveal that patients who have high levels of meaning of life, peace, and faith could be seem to have an ability to regulate their emotions, thus not becoming depressed so easily …”
Section: Discussionmentioning
confidence: 84%
“…Planning spiritual care should include spiritual well‐being in conjunction with standard healthcare treatments, and modify the treatment plan as needed based on patients spiritual needs . Implementing spiritual interventions can include various actions such as encourage relationship between the patient and his or her family, reading spiritual materials (Quran or Athkar), utilizing humor, utilizing meditation or praying, or discussing with patients how to maintain inner peace, contribute to society, cope with life's stressors, and feel the connection with nature . Moreover, spiritual interventions should be provided based on empathy and nonjudgmental love, affirm the worth dignity, nobility and humanistic desire of each person, and its response to both religious and nonreligious needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation